Temperature stresses in prismatic substances at radiant-convective heat exchange - Ju. S. Postolnik; V. I. Timoshpolskij; O. A. Chernyj; D. N. Andrianov (Литьë и металлургия)
There is given the solution of linked problem of heat conduction and thermoelasticity at heating of prismatic substances by radiant convection current, based on using of the method of equivalent sources.